Psychiatric Comorbidities in HIV-Positive Patients: A Literature Review - Czechowicz, Marta; Madoń, Joanna; Gadziński, Patryk (Journal of Education, Health and Sport, 2025)
Background People living with HIV (PLWH) experience psychiatric comorbidities far more frequently than the general population, with prevalence estimates ranging from 1.5 to 8 times higher. These mental health conditions substantially impact treatment adherence, viral suppression, and overall quality of life. Aim This literature review aimed to provide an updated, comprehensive overview of psychiatric comorbidities in people living with HIV and their underlying biological and psychosocial mechanisms. Materials and Methods This article systematically reviews the existing literature on psychiatric comorbidities among HIV-positive patients. A comprehensive database search was conducted using Web of Science, PubMed, and Google Scholar. The bibliographies of cited works were also reviewed. The literature review and article selection process concluded in October 2025. Results To the most prevalent psychiatric disorders among PLWH belong depression (31%), posttraumatic stress disorder – PTSD (28%), anxiety disorders (20-40%), substance use disorders – SUD (40-74%), and HIV-associated neurocognitive disorders – HAND (45%). Psychiatric comorbidities in PLWH result from complex interactions between biological mechanisms – including HIV's affinity for neural tissue, chronic neuroinflammation mediated by cytokines such as IL-6 and TNF-α, and reduced monoamine availability – and psychosocial factors, particularly internalized stigma, discrimination, and trauma related to HIV diagnosis. Conclusions Early health screening and implementation of mental health services within HIV treatment improve psychiatric outcomes and ART adherence.